Gruppenaufnahme - Thomas Köhler
Bundeswirtschaftsminister Werner Müller; Bundesarbeitsminister Walter Riester; Bundeslandwirtschaftsminister Karl-Heinz Funke; Bundesfamilienministerin Christine Bergmann; Bundesjustizministerin Herta Däubler-Gmelin;